A click-chemistry based approach for the synthesis of new BODIPY-labelled fluorescent ligands - Speed, Daniel (2013)
Fluorescent ligands have found numerous applications for studying interactions of drug molecules with their target and as a probe of biological systems. A common approach when designing and synthesising a fuorescent ligand is to separate the fluorophore and pharmacophore via a linker. One novel approach is to utilise click chemistry to allow the coupling of fluorophore to a pharmacophore. This thesis reports the results of an investigation into utilising click chemistry, specifically the alkyne-azide copper (I) cycloaddition to synthesis novel fluorescent GPCR ligands. Targets included the β1, β2 adrenoceptor and the muscarinic M3 receptor.